Identification of Genes Regulating Cell Death in Staphylococcus aureus - Yee, Rebecca; Feng, Jie; Wang, Jiou; Chen, Jiazhen; Zhang, Ying (Frontiers in Microbiology, 2019)
Staphylococcus aureus is an opportunistic pathogen that causes acute and chronic infections. Due to S. aureus' s highly resistant and persistent nature, it is paramount to identify better drug targets in order to eradicate S. aureus infections. Despite the efforts in understanding bacterial cell death, the genes and pathways of S. aureus cell death remain elusive. Here, we performed a genome-wide screen using a transposon mutant library to study the genetic mechanisms involved in S. aureus cell death. Using a precisely controlled heat-ramp and acetic acid exposure assays, mutations in 27 core genes (hsdR1, hslO, nsaS, sspA, folD, mfd, vraF, kdpB, USA300HOU_2684, 0868, 0369, 0420, 1154, 0142, 0930, 2590, 0997, 2559, 0044, 2004, 1209, 0152, 2455, 0154, 2386, 0232, 0350 involved in transporters, transcription, metabolism, peptidases, kinases, transferases, SOS response, nucleic acid and protein synthesis) caused the bacteria to be more death-resistant. In addition, we identified mutations in 10 core genes (capA, gltT, mnhG1, USA300HOU_1780, 2496, 0200, 2029, 0336, 0329, 2386, involved in transporters, metabolism, transcription, cell wall synthesis) from heat-ramp and acetic acid that caused the bacteria to be more death-sensitive or with defect in persistence. Interestingly, death-resistant mutants were more virulent than the parental strain USA300 and caused increased mortality in a Caenorhabditis elegans infection model. Conversely, death-sensitive mutants were less persistent and formed fewer persister cells upon exposure to different classes of antibiotics. These findings provide new insights into the mechanisms of S. aureus cell death and offer new therapeutic targets for developing more effective treatments for infections caused by S. aureus.